2021
DOI: 10.1097/md.0000000000026502
|View full text |Cite
|
Sign up to set email alerts
|

Reflux esophagitis is associated with higher risks of acute stroke and transient ischemic attacks in patients hospitalized with atrial fibrillation

Abstract: Reflux esophagitis (RE) is a subset of gastroesophageal reflux disease (GERD) with endoscopic evidence of esophageal inflammation, which has been linked to an increased incidence of atrial fibrillation (AF). However, data on the effect of RE on patient outcomes is limited. We sought to examine the potential association of RE with outcomes of patients with AF in a nationwide study. The National Inpatient Sample (NIS) database was queried to identify hospitalized adult patients with AF and RE between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…49 Prospective studies are necessary to investigate this association and to establish whether anti-TNF therapy can effectively protect against PD. Notably, concordant with an earlier study that linked reflux oesophagitis to an increased risk of stroke and transient ischaemic attack in patients with atrial fibrillation, 21 the risk of CVD in our study was significantly greater after a diagnosis of GORD, CD and MC. These findings suggest that a better understanding of the link between GI inflammation and cerebrovascular events may lead to improved risk stratification and identification of new preventive strategies.…”
Section: Gut Brain Axissupporting
confidence: 93%
See 2 more Smart Citations
“…49 Prospective studies are necessary to investigate this association and to establish whether anti-TNF therapy can effectively protect against PD. Notably, concordant with an earlier study that linked reflux oesophagitis to an increased risk of stroke and transient ischaemic attack in patients with atrial fibrillation, 21 the risk of CVD in our study was significantly greater after a diagnosis of GORD, CD and MC. These findings suggest that a better understanding of the link between GI inflammation and cerebrovascular events may lead to improved risk stratification and identification of new preventive strategies.…”
Section: Gut Brain Axissupporting
confidence: 93%
“…These findings suggest that a better understanding of the link between GI inflammation and cerebrovascular events may lead to improved risk stratification and identification of new preventive strategies. 21 After Grey et al first discovered that α-synuclein was most abundant in the appendiceal mucosa, 9 conflicting evidence has emerged about the impact of an appendectomy on PD risk. While three studies did not find any association, 11 14 50 one abstract reported an increased risk of PD 13 and two large observational studies supported a protective effect.…”
Section: Gut Brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further exploration of the potential relationship between the two diseases is increasingly important to prevent and treat them. Several clinical observational studies in recent years have shown that GERD can increase the risk of stroke in different groups of people, such as regular GERD patients, young adult GERD patients, and GERD patients with atrial fibrillation ( 7 , 8 , 21 ). Similarly, a population-based cohort study also found that stroke patients had a higher risk of GERD ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A population-based follow-up study suggests that young patients with gastric reflux esophagitis are at higher risk of stroke ( 7 ). An analysis of inpatient samples also found that reflux esophagitis increased the incidence of acute stroke in patients with atrial fibrillation ( 8 ). It has long been considered that there may be a link between GERD and stroke.…”
Section: Introductionmentioning
confidence: 99%